Evolution of the environmental microbiota of a new neonatal intensive care unit (NICU) and implications for infection prevention and control. (28th February 2021) - Zachariah, Philip; Rozenberg, Felix D.; Stump, Stephania; Moscoso, Dagmara I.; Krishnamurthy, Ganga; Saiman, Lisa; Uhlemann, Anne-Catrin; Freedberg, Daniel E.
Abstract: Objective: To describe changes in the environmental microbiota of a new neonatal intensive care unit (NICU) and potential implications for infection prevention and control (IPC) efforts. Design: Prospective observational study. Setting: A newly constructed level IV neonatal cardiac intensive care unit (NCICU) before and after patient introduction and the original NICU prior to patient transfer. Methods: Environmental samples were obtained from the original NICU prior to patient transfer to a new NCICU. Serial sampling of patient rooms and provider areas of the new NICU was conducted immediately prior to patient introduction and over an 11-month study period. Microbiota at each sampling point were characterized using Illumina sequencing of the V3/V4 region of the 16S rRNA gene. Microbiota characteristics (α and β diversity and differential abundance) were compared based on time, location, and clinical factors (room-level antibiotic use and patient turnover). Results: An immediate increase in the environmental differential abundance of gut anaerobes were seen after patient introduction. There was an increase in the relative abundance of Staphylococcus spp, Klebsiella spp, Pseudomonas spp, and Streptococcus spp over time. The new NCICU consistently showed more diverse microbiota and remained distinct from the original NICU. The microbiota of the provider areas of the NCICU eventually formed a cluster separate from the patient rooms. Patient turnover increased room-level microbiota diversity. Conclusion: Microbiota characteristics of the new NICU were distinct from the original ICU despite housing similar patients. Patient and provider areas developed distinct microbiota profiles. Non–culture-based methods may be a useful adjunct to current IPC practice.